Promise and perils of water reform: Perspectives from Northern Ghana - Wolfram Laube (University of Bonn, Center for Development Research (ZEF), 2005)
In 1996, the Ghanaian government has started a water reform process, which put the countries water resources under the control of the Water Resources Commission (WRC). This appointed commission consists of representatives of water providers, statutory regulatory agencies, irrigation officials, NGOs, women and traditional authorities. This commission has been assigned the task to ensure the economically efficient, ecologically sustainable, socially equitable and gender sensitive development of the country's water resources. Using patterns of resource management in the irrigation sector of northern Ghana as example, this article shows that serious obstacles towards the local implementation of the water reform exist. Currently the management and allocation of resources is largely disobeying the regulations, rules and laws set out by various official agencies. Competing local authorities and institutions, lacking legitimacy and enforceability of official rules, as well as corruption, nepotism and political clientelism make resource management prone to conflicts, contestations and renegotiations. Non-transparent and irresponsible resource management compromises the efficiency, sustainability and equity of the irrigation sector. As the WRC lacks the competencies and resources to manage water resources at the local level, but has to rely on already existing structures the prospects for the implementation the water reform remains therefore questionable.
urn:nbn:de:0202-20080911103
Keywords: 330